STAT6 Mediates Footpad Immunopathology in the Absence of IL-12p40 Following Infection of Susceptible BALB/c Mice With Leishmania major - Kauffmann, Florence; Meert, Elyn; de Jonge, Kaat; Elkrim, Yvon; Hanot Mambres, Delphine; Denis, Olivier; Muraille, Eric; Magez, Stefan; De Trez, Carl (Frontiers in Immunology, 2018)
Leishmania major (L. major) parasites are intracellular parasites belong to the Trypanosomatidae family and are the causative agent of cutaneous leishmaniasis. This disease affects approximately 1.5 million per year worldwide and there is currently no prophylactic vaccine available. L. major is transmitted by the bite of an infected sandfly and has been considered for decades now as a mouse model of choice to identify the factors implicated in Th1 and Th2 polarization due to the natural resistance and susceptibility to infection of C57BL/6 and BALB/c mice, respectively. In this study, we refine the role of IL-12p40 cytokine, which is implicated the development of a protective Th1 response, and STAT6, a transcription factor involved in the signaling via detrimental IL-4 and IL-13 associated Th2 cytokines during L. major infection in the BALB/c model. In the absence of STAT6 and IL-12p40 signaling, double knock-out (DKO) susceptible BALB/c mice displayed reduced footpad swelling and ulcerative lesion compared to IL-12p40-/- mice upon L. major infection. Hence, they expressed slower upregulation of keratinocyte markers implicated in the inhibition of wound healing, such as Krt6a and Krt16. This coincides with the presence of neutrophils displaying an altered phenotype characterized by a lower expression of surface markers Ly6C, CD11b and Ly6G. These neutrophils exhibited very lower levels of apoptosis similarly to neutrophils present in resistant STAT6-/- mice. Interestingly, the reduced footpad swelling in DKO mice is associated with a high footpad parasite level similar to susceptible IL-12p40-/- mice. In conclusion, this study demonstrate that in the absence of both STAT6 and IL-12p40 signaling, L. major-infected mice display smaller and less ulcerated lesions, which does however not correlate with reduced parasite load. In addition, the presence of neutrophils with an altered phenotype is associated to reduced apoptosis and delayed immunopathologies, demonstrating the detrimental role of STAT6 in infected susceptible BALB/c mice.